Javaslat a trimesztriális rendszer bevezetésére – A debreceni jog- és államtudományi kar felterjesztésé gróf Zichy János vallás- és közoktatásügyi miniszterhez (1918. augusztus 1.) - Király, Sándor (Gerundium, 2019)
Proposal for the Introduction of the Trimester System – Proposal by Faculty of Law of the University of Debrecen to Earl János Zichy, Minister of Religion and Public Education. The Faculty of Law of the University of Debrecen in the last period of the World War I. made a proposal in order to divide the school year to three semester. It was a strange source of the history of the Hungarian higher education. Based on this document can be cognizable the real life and thinking of the students of the university who came back from the war and of the professors who met with them the first time. The trimestrial system of the higher education was favoured by the students too, but it wasn’t able to come to real because the collapse of the Monarchy.